2021
DOI: 10.1155/2021/8960190
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Wind Characteristics and Wind Power Potential of Gharo, Pakistan

Abstract: The objective of this research work is to assess the wind characteristics and wind power potential of Gharo site. The wind parameters of the site have been used to calculate the wind power density, annual energy yield, and capacity factors at 10, 30, and 50 m. The wind frequency distribution including seasonal as well as percentage of seasonal frequency distribution has been investigated to determine accurately the wind power of the site. The coefficient of variation is calculated at three different heights. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 51 publications
0
13
0
Order By: Relevance
“…The energy obtained from a wind turbine can be calculated by equation (19). While substituting the equation (2) with equation (18) which can be read as 19 (Hulio, 2021a; Hulio, 2021b): …”
Section: Methods and Site Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…The energy obtained from a wind turbine can be calculated by equation (19). While substituting the equation (2) with equation (18) which can be read as 19 (Hulio, 2021a; Hulio, 2021b): …”
Section: Methods and Site Descriptionmentioning
confidence: 99%
“…The capacity factor is an important measure of the performance of wind turbines that can be expressed as follows (Hulio, 2021a): …”
Section: Methods and Site Descriptionmentioning
confidence: 99%
“…The recent studies of wind resource and economic assessment of this region has been given in following literature (Hulio, 2020;Hulio et al, 2021aHulio et al, , 2021bHulio and Jiang, 2020). The wind resource and energy economic assessment of Gharo site has been carried out at 10, 30 and 50 m. The authors concluded that the site is suitable for isntalling the utility wind turbines (Hulio, 2021). In another wind resource assessmnet of Karachi Port Trust (KPT) has been carried at 10 and 30 m that showed site has potential for energy output (Hulio and Jiang, 2020).…”
Section: Wind Energymentioning
confidence: 99%
“…These energy sources are clean and environmentally friendly. Green energy (renewable energy) plays an important role to have affordable, accessible, and reliable energy for all (Hulio, 2021). Renewable energy diversifies the energy source and reduces the utilization of fossil fuels.…”
Section: Introductionmentioning
confidence: 99%